Edukasi Pencegahan Stunting Berbasis Aplikasi Android Dalam Meningkatkan Pengetahuan Dan Sikap Ibu - ELFIZA FITRIAMI; Achmad Vindo Galaresa (Citra Delima Scientific journal of Citra Internasional Institute, 2022)
One of the problems of growth and development in toddlers is stunting. Stunting or low TB/U index is caused by socio-economic conditions, maternal nutrition during pregnancy, comorbidities in infants, lack of nutritional intake in infants and parenting patterns, and education level of parents of children under five. Indonesia is a developing country that contributes to the growth of stunting in children under five in the world, where Indonesia is currently ranked fifth in stunting in children under five in the world. Based on UNICEF data (2020) it states that the number of stunting events has increased globally by 15% due to COVID-19 in 2020. Meanwhile, data according to the Indonesian Ministry of Health states that the incidence of stunting is quite high, namely, 27.67% in 2020. The purpose of the study is to determine the effect of android application-based stunting education to increase mothers' knowledge and attitudes so that stunting in children under two years can be prevented. The sampling technique used is purposive sampling. The tools that will be used are android-based media applications, WHO anthro software, weight scales, microtome, and questionnaires. Data analysis using a non-parametric test (Wilcoxon). The study was conducted at the Tenayan Raya Pekanbaru Health Center with a sample of 54 respondents. There is an effect of stunting education using an android application (p) 0.0001<0.05 on increasing knowledge and attitudes of mothers at the Tenayan Raya Public Health Center Pekanbaru.